Analisis Hukum Terhadap Perubahan Mekanisme Pengadaan Langsung dalam Perpres Nomor 46 Tahun 2025, tentang Perubahan Kedua atas Peraturan Presiden Nomor 16 Tahun 2018 tentang Pegadaan/Jasa Pemerintah - Tri Wahyudi; Jamri; Bambang Sasmita Adi Putra (PT PUSTAKA CENDEKIA GROUP, 2026)
This study examines the changes to the direct procurement mechanism under Presidential Regulation Number 46 of 2025 concerning the Second Amendment to Presidential Regulation Number 16 of 2018 on Government Goods and Services Procurement. This research employs a normative legal method with a descriptive-analytical approach, utilizing statutory, conceptual, and analytical frameworks. Three research questions are analyzed: the substantive changes to the direct procurement mechanism, the legal analysis from the perspectives of legal certainty and good governance principles, and the implications for effectiveness, transparency, and accountability in government procurement. The findings indicate that Presidential Regulation Number 46 of 2025 introduces significant normative changes through mandatory full digitalization, strengthened procurement officer competency requirements, expanded scope to village governments, and increased direct purchase thresholds for construction works. Reviewed from legal certainty theory, the regulation clarifies norms although transitional challenges require careful management. From a good governance perspective, the digitalization of direct procurement simultaneously reinforces transparency, accountability, and effectiveness. The study concludes that these changes signify a paradigmatic transformation in government procurement toward data-driven governance that is openly accountable to the public.